U-SHAPED ASSEMBLY LINE BALANCING WITH TEMPORARY WORKERS - Nakade, Koichi; Ito, Akiyasu; Ali, Syed Mithun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
U-shapedassembly lines are useful in an efficient allocation of workers tostations. In assembly lines, temporary workers are placed to correspond to thefluctuation of demand. Sets of feasible tasks for temporary workers aredifferent from those of permanent workers. The tasks which are familiar to permanent workers also vary. For the U-shaped assembly balancing problem under these situations the optimal cycle times for a given numberof temporary workers and the optimal number of workers for given cycle time arederived and compared between U-shaped line balancing and straight linebalancing. We also discuss the optimal allocation for a single U-shaped lineand two U-shaped lines. In several cases, in particular when high throughputsare required, it is shown numerically that the number of temporary workers inoptimal allocation for two lines is less than that of optimal allocation for asingle line.